The relationship between high-signal intensity changes in the glenohumeral joint capsule on MRI and clinical shoulder symptoms - Atsushi Tasaki; Taiki Nozaki; Wataru Morita; Daiki Kobayashi; Barry B. Phillips; Nobuto Kitamura (Elsevier, 2020)
Background/objective: High-signal intensity changes in the glenohumeral joint capsule on T2-and proton density-weighted magnetic resonance imaging are known as characteristic finding that is often observed in patients with frozen shoulder. We investigated the associations between high-signal intensity changes in the joint capsule on magnetic resonance imaging and the presence of rotator cuff tears and shoulder symptoms in patients with shoulder pain. Methods: The medical records of 230 patients with shoulder pain who underwent magnetic resonance imaging at our hospital were reviewed. Patients were divided into three groups according to the presence and/or degree of rotator cuff tears (none, partial, or complete). The frequency of high-signal intensity changes in the joint capsule and its relationship with shoulder symptoms and the severity of rotator cuff tears were assessed. By quantitatively evaluating the intensity on MRI, the ratio between the joint capsule and the long head of the biceps (HSIC ratio) was calculated and compared with 15 healthy subjects. Results: High-signal intensity changes were diagnosed in 165 (72%) patients, and it was significantly associated with night pain and range of motion limitation (p < 0.01). High-signal intensity changes were present in 66 patients (70%) with no rotator cuff tears, in 69 (71%) with partial rotator cuff tears, and in 36 (80%) with complete rotator cuff tears, without differences in their occurrence (p = 0.60), but were significantly associated with night pain in all the groups (p < 0.01) without differences in tear severity (p = 0.63). The ratio in the high-signal intensity changes (HSIC) positive group was approximately six times higher than that in the HSIC-negative and control groups (P < 0.01). Multivariate logistic regression analysis revealed that night pain is significantly associated with high-signal intensity changes (p < 0.01). Conclusion: Shoulder pain is a common and reliable clinical finding in patients with high-signal intensity changes, regardless of the presence and/or degree of rotator cuff tears, Such changes may indicate night pain and range of motion limitation in patients.